Effect of IBA concentrations on semi-hard wood cuttings of phalsa cv. Thar Pragati (Indian Journal of Arid Horticulture, 2021)
An experiment was conducted at Central Horticultural Experiment Station (lCAR-CIAH), Vejalpur on vegetative propagation of phalsa through semi hardwood stem cuttings in the month of July. The cuttings were treated with different concentrations of IBA (JOO, 150, 500, 1000, 2000, 3000, 4000 and 5000 ppm) along with control and the experiment was replicated thrice. Treated cuttings were planted in poly bags containing soil, sand and FYM in equal proportion and kept in open conditions. Semi hardwood cuttings when treated with IBA 2000 ppm resulted in the highest survival percentage (50.20 %), length of sprout (76.30 cm), number of primary roots (16.30) number of secondary roots (32.20), number of leaves/plan t (15.21), number of sprout/plant (3.90) and girth of sprout (l.90 cm) 150 days after treatment, it was followed by IBA1000 ppm. Whereas control recorded the minimum survival percentage (22.12 %), length of sprout (40.20 cm), number of primary roots (6.20) and number of secondary roots (17.00), number of leaves/plant (7.0), number of sprout/plant (1.70) and girth of sprout (1.20cm) 150 days after treatment.